The Role of Media in Preserving Tribal Communities in Varanasi - GP Pandey (Journal of Advanced Research in Journalism & Mass Communication, 2025)
The media is playing a vital role in the field of social science research. This is the platform by which people easily collect and share information. Media in the 21st century is the main part of the society to reach from the local to the urban level, and also media is playing a very important role in highlighting the tribe culture in Varanasi. This study aims to explore the deep influence of media on the tribal culture of Varanasi, a holy city known as the capital of spirituality and for that cultural, religious, and historical significance. "Tribe": a group of people living in any society defined by their culture, lifestyle, language, food, and clothing for a long time. From this study we will come to know the dynamics of tribal communities like Gond, Musahar, Chero, and Kharwar of Varanasi and also find how media focusing on both the modern and traditional affects their cultural practices, socio-economic conditions, and traditions. The study employs descriptive and exploratory methods, with a focus on social and cultural values analysis, social features with structure, and a functional approach in the media field.